The Ateni Sioni Church: Sacred Architecture and the Languages of Power in Medieval Iberia - Khakhanova, Margarita (Eikón / Imago, 2026)
This article explores the medieval Iberian Ateni Sioni Church, built in the 7th century and renowned for its comprehensive mural cycle dated to the 12th century. It draws particular attention to the church’s architectural, topographical, and decorative parallels with a significant sacred site in Iberia, the Church of the Holy Cross in Jvari. Rather than viewing these similarities as exclusively formal, the article offers an alternative perspective, focusing especially on the church’s topography and exterior decoration. It examines the donor reliefs on the facade in relation to their spatial context and considers how pilgrims and worshippers engaged with them as well as their possible symbolic significance at the time of their creation. The study demonstrates that, in the medieval period, Ateni Sioni served not only as a religious monument but also as a powerful political statement – a visual embodiment of authority and faith.